Medical Diagnostic Models - Bozorov Erkin Hodjievich; Kubaev Asaliddin Esirgapovich (Scholars Digest Publishing, 2023)
In this article, in the course of explaining the topic, students will be presented with positive scientific results obtained using the BLITZ-SURVEY method, and a description of the method will be shown.
Keywords: diagnostic models in medicine, modeling, medical diagnostics, blitz-survey, DataMining, Rational models, Amazon, Alisa, Apple, Siri, Yandex.